Sustainable and responsible entrepreneurship and key drivers of performance - Popescu, Cristina Raluca Gh., 1983-; Verma, Rahul, 1989- (Advances in business strategy and competitive advantage., 2021)
"This book provides an updated view of the newest trends, novel practices and latest tendencies concerning the sustainable and responsible entrepreneurship, in a world permanently dominated by insecurity and dramatic economic, political, and managerial changes"--